2008
DOI: 10.1177/1012690208095378
|View full text |Cite
|
Sign up to set email alerts
|

Negotiations of Being and Becoming

Abstract: This paper is based on new empirical, qualitative research with minority ethnic rugby league players in the South-West of France. Drawing on similar research on rugby league in the north and the south of England, the paper examines how rugby league, traditionally viewed as a white, working class male game (Collins, 2006;Denham, 2004;Spracklen, 1995Spracklen, , 2001) has had to re-imagine its symbolic boundaries as they are constituted globally and locally to accommodate the needs of players from minority ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Its symbolic boundaries are constructed by a belief that we are all individuals, that metal is more authentic than pop. Just as rugby league fans wear Les Catalans jerseys and polo-shirts to demonstrate they are authentic fans who understand the importance of southern France in our history (Spracklen and Spracklen 2008), metal fans prove their level of belonging in the imaginary community by wearing obscure band t-shirts. 4 If one wears something associated with black metal, one indicates one is so committed to being an individual and being out of the mainstream that anything might be possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its symbolic boundaries are constructed by a belief that we are all individuals, that metal is more authentic than pop. Just as rugby league fans wear Les Catalans jerseys and polo-shirts to demonstrate they are authentic fans who understand the importance of southern France in our history (Spracklen and Spracklen 2008), metal fans prove their level of belonging in the imaginary community by wearing obscure band t-shirts. 4 If one wears something associated with black metal, one indicates one is so committed to being an individual and being out of the mainstream that anything might be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Hobsbawm showed that these states invented traditions they used to attempt to impose their hegemony other expanding populations at the time of the industrial revolution and the clash of European empires. When I read Kalman-Lamb's paper I was excited because I have been making the same use of Anderson and Hobsbawm to understand sports fandom and other forms of fandom ever since I started my PhD in 1993 (Spracklen 1995;1996;2007;2011a;Spracklen and Spracklen C. 2008;Spracklen and Spracklen L. 2021;Spracklen, Lucas and Deeks 2014;Spracklen, Timmins and Long 2010). But I was disappointed that Kalman-Lamb did not cite any of that work.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of articles in IRSS have also examined sports in migration or the role of sports for minority ethnic and diaspora groups (e.g., Bradbury 2010, Burdsey 2010, Campbell and Williams 2013, Fletcher 2011, Krouwel et al 2006, Joseph 2012, Spracklen and Spracklen 2008, Thangaraj 2010). In the wake of the so-called refugee crisis around 2015, such literature has expanded further (e.g., Buser et al 2021, Dowling 2019, Kyeremeh 2019, McSweeney and Nakamura 2019.…”
Section: State Of the Art; Through The Lens Of Irssmentioning
confidence: 99%
“…Scholars (Burdsey, 2011; Doidge et al, 2020a) have contended that belonging in sport is not only impacted by institutional policies but also by a sport organisation's own culture and practices. In this context, literature has shown that for racialised minorities in the Global North, belonging is not necessarily an outcome of sport participation (Burdsey, 2011; Spracklen and Spracklen, 2008). Burdsey, for example, has documented how colour-blind ideology and persistence of ‘racial microaggressions’ in first-class cricket in England contribute to the marginalisation of players from ethnic minority backgrounds.…”
Section: Sport Forced Migration and Belongingmentioning
confidence: 99%